(untitled) (Siddhajyoti Interdisciplinary Journal, 2026)
This research examines English teachers’ perceptions and experiences of utilising ChatGPT to enhance teaching in secondary-level Nepalese classrooms. To obtain the data, a qualitative narrative research method was adopted, involving four English teachers who have been dealing with ChatGPT. Semi-structured interviews, class observations, and reflective narratives were employed to gather teachers’ experiences with an AI tool in their classrooms. The collected data were thematically analysed and revealed positive outcomes, including students’ engagement, individual learning, and language proficiency with skills. However, it identified challenges, including limited resources, economic constraints, a lack of training and a human workforce, as well as dependency on these tools, and issues with ICT policy and the management of these tools. This study highlights the importance of integrating AI tools into Nepalese classrooms in the digital age. It provides significant insights for teachers to enhance their teaching and learning, resource management, and learning achievement, as well as promote digital literacy. This research makes significant contributions and yields fruitful outcomes for educators and policymakers to integrate ChatGPT and implement effective management strategies for development plans and the use of such technologies in English language teaching within Nepalese classroom practices in community schools.